Spatial Analysis of Open Unemployment Rate in West Java Province Using the Spatial Autoregressive Model - Zulfadly Harman Harahap; Tessy Octavia Mukhti (Departemen Statistika Universitas Negeri Padang, 2026)
Unemployment remains a major socio-economic issue in West Java Province. The Open Unemployment Rate (OUR) is affected not just by local regional elements but also by the circumstances of adjacent regions, showing that spatial interdependence exists.The research aims to analyze the spatial pattern of OUR in West Java and identify the influencing factors using the Spatial Autoregressive (SAR) approach. The study uses cross-sectional secondary data from all regencies and cities in West Java for the year 2023. Moran’s I findings indicate a positive spatial dependence, suggesting that regions with high OUR are typically surrounded by regions with similarly high unemployment rates. According to the analysis using the Lagrange Multiplier test, the SAR model was chosen. Estimation results show that population growth rate and government expenditure significantly affect OUR. Additionally, the spatial lag coefficient shows a positive and significant value, suggesting spatial spillover effects. These findings highlight the importance of incorporating spatial perspectives in formulating regional employment policies.